Messages Communication in the Al-Qur’an (Study of Messages in the Al-Qur'an for Believers) - Hasbullah Hasbullah; Muntasir Muntasir; Saiful Bahri; Riska Zahara; Zulfia Zulfia (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
Not all of the verses in the Al-Quran that are historical and normative can be understood only textually, because many of the verses in the Al-Quran still have broad (universal) meanings and need to be interpreted deeper, so that a law or wisdom that can be understood and practiced by all humans in general and Muslims in particular. From the peel of this verse several conclusions can be drawn, including namely; Al-Quran is the source of Islamic communication. Because all the elements of Islamic communication are contained in the Al-Quran, among these elements are misage or message. There are so many terms in the Al-Quran that relate to misage of communication. Among them as contained in Surat At-Tahrim verse 6; where the message of Islamic communication in the verse is, Allah reminds the believers to protect themselves, their families from the fires of hell. In addition, the message of Islamic communication contained in Surat Al-Baqarah verse 208; the Al-Quran orders every believer to practice the teachings of Islam perfectly. In other words, Muslims must apply Islamic law in every aspect of their lives.